The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/f12050530
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Supply and Demand for Coloured Wood Products? An Empirical Study in Slovakian Practice

Abstract: The paper deals with the issue of the colour tones of wood and furniture products. The main aim is to identify the supply of the colour tones of wood and furniture products and to map the interest in these wood colour tones at potential customers in Slovakia. By means of two independent surveys of supply and demand for colour tones of wood and furniture products, various shortcomings have been identified. It is necessary to increase the supply of wood and furniture products with the natural colour of the wood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Similarly, the increase in labor costs of woodworking and wood-based material producers in Central Europe forces manufacturers to use higher processed materials to reduce the share of these costs in the total production cost of the final product [66]. Our finding can also be associated with the finding of Sedliačiková et al [73], the current demand for colored wood was considerably higher than the supply of such products in the Slovak market.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, the increase in labor costs of woodworking and wood-based material producers in Central Europe forces manufacturers to use higher processed materials to reduce the share of these costs in the total production cost of the final product [66]. Our finding can also be associated with the finding of Sedliačiková et al [73], the current demand for colored wood was considerably higher than the supply of such products in the Slovak market.…”
Section: Discussionsupporting
confidence: 70%
“…Colour is often a decisive element as it influences the aesthetic of products [30,31]. The effect of heat treatment on wood colour consisted of darkening.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important when wood is not expected to be exposed to sun and undergo color changes, as the initial aspect modification will not be attenuated over time. Conversely, as stated by Sedliaciková [302], a significant proportion of the public is in fact looking for colored wood. While dyes and pigments are commonly used for this purpose, innovative new methods were developed over the last few years to obtain colored wood surfaces.…”
Section: Economical Aspectsmentioning
confidence: 99%
“…The visual aspect of wood is also a crucial element for wood surface treatments. Different studies have shown that the appearance of wood is of foremost importance to the consumer [300,301], and the natural aspect of wood is usually well appreciated [302,303]. In regard to wood surface treatments, they represent an extra challenge to efficiently protect wood, as transparent surfaces cannot block UV radiations, which can lead to the photodegradation of the wood polymeric constituents and the delamination of clear coatings [24].…”
Section: Economical Aspectsmentioning
confidence: 99%